2015
DOI: 10.1530/rep-14-0618
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of bovine cystic ovarian disease pathogenesis

Abstract: Cystic ovarian disease (COD) is one of the main causes of reproductive failure in cattle and causes severe economic loss to the dairy farm industry because it increases both days open in the post partum period and replacement rates due to infertility. This disease is the consequence of the failure of a mature follicle to ovulate at the time of ovulation in the estrous cycle. This review examines the evidence for the role of altered steroid and gonadotropin signaling systems and the proliferation/apoptosis bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 168 publications
1
39
0
Order By: Relevance
“…For this reason, it can be speculated that the ovulatory follicles developed in cows with a history of pathologic puerperium have a reduced capacity to trigger the preovulatory LH surge. Although the etiology of OFC has not been established, the absence or insufficiency of the preovulatory LH surge is considered to be a crucial factor in the development of this condition (Peter 2004, Ortega et al 2015.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, it can be speculated that the ovulatory follicles developed in cows with a history of pathologic puerperium have a reduced capacity to trigger the preovulatory LH surge. Although the etiology of OFC has not been established, the absence or insufficiency of the preovulatory LH surge is considered to be a crucial factor in the development of this condition (Peter 2004, Ortega et al 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Ovarian activity was synchronized starting with the procedure commonly referred to as G6G (Pursley et al 1995, Bello 2006, Díaz et al 2015 with some modification, and only cows with one or more corpora lutea identified by transrectal ovarian ultrasonography were selected. The synchronization protocol consisted of two doses of prostaglandin F2α (PGF2α; 150 µg D+cloprostenol; Enzaprost DC, Biogénesis-Bagó, Garín, Buenos Aires, Argentina) administered 12 h apart on day 0 to induce luteolysis (Hatler et al 2008), followed by a dose of GNRH (20 µg buserelin acetate; Gonaxal, Biogénesis-Bagó, Argentina) 2 days later to stimulate ovulation of the preovulatory follicles present.…”
Section: Induction Of Follicular Persistence By Progesterone Administmentioning
confidence: 99%
“…Control cows did not receive any additional hormonal treatment. On day 16 after estrus synchronization, cows of groups P5, P10 and P15 were treated with an intravaginal progesterone device (750 mg micronized progesterone; Pro-Ciclar P4-Zoovet, Santa Fe, Argentina) inserted 1 day after the first PGF2α injection of Ovsynch to obtain subluteal concentrations of progesterone (1-2 ng/mL), as described by Bigelow & Fortune (1998) and Díaz et al (2015). On an average, ovulation occurred around 4 days after administration of the first PGF2α dose (range 101-106 h).…”
Section: Induction Of Follicular Persistence By Progesterone Administmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of ovarian cysts is known to be related to alterations in apoptosis and steroid production in the ovarian follicle (Ortega et al, 2015).…”
Section: Regulation Of Steroidogenesismentioning
confidence: 99%